2012
DOI: 10.1177/0363546512449816
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Running on Knee Articular Cartilage and Meniscus Magnetic Resonance Relaxation Times in Young Healthy Adults

Abstract: Background Understanding the acute response of healthy knee cartilage to running may provide valuable insight into functional properties. In recent years, quantitative magnetic resonance (MR) imaging techniques (T1ρ and T2 relaxation measurement) have shown tremendous potential and unique ability to noninvasively and quantitatively determine cartilage response to physiologic levels of loading occurring with physiologic levels of exercise. Purpose To measure the short-term changes in MR T1ρ and T2 relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 38 publications
13
130
3
Order By: Relevance
“…A recently published analysis of T 2 of the hyaline cartilage in a healthy study population revealed mean values of 20-30 ms in the deep layer and 40-50 ms in the superficial layer of the femoral condyle with an arthroscopically normal articular cartilage. 14 In comparison with our results, Subburaj et al 19 found similar T 2 values with a mean T 2 relaxation time of 31.7 ms (63.9 ms) in 20 young healthy volunteers (age 28.7 years; 22-35 years).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A recently published analysis of T 2 of the hyaline cartilage in a healthy study population revealed mean values of 20-30 ms in the deep layer and 40-50 ms in the superficial layer of the femoral condyle with an arthroscopically normal articular cartilage. 14 In comparison with our results, Subburaj et al 19 found similar T 2 values with a mean T 2 relaxation time of 31.7 ms (63.9 ms) in 20 young healthy volunteers (age 28.7 years; 22-35 years).…”
Section: Discussionsupporting
confidence: 88%
“…For the assessment of the immediate influence of athletic loading on cartilage relaxation times, only T1rho and T 2 have been applied and investigated so far. 19,20,27 One previous investigation of Subburaj et al 19 The authors observed a slight increase of relaxation times immediately after the run, but they returned to approximately prerun values after 2 h. As an explanation, the authors argue that they analyzed actual running in an in vivo study design instead of passive knee bending. These findings are contrary to our results and to the above-mentioned publications, although the study designs are comparable.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One such type is deep water running (DWR), otherwise known as aqua jogging, which consists of simulated running in deep water. DWR is utilized for a variety of populations including the elderly, obese individuals, individuals with orthopaedic injuries, athletes, healthy individuals, as well as many persons with various clinical conditions (Subburaj et al, 2012;Killgore, 2012;Cuesta-Vargas et al, 2012;Azevedo, Lambert, Zogaib, & Barros Neto, 2010;Kaneda, Sato, Wakabayashi, Hanai, & Nomura, 2008;Broman, Quintana, Lindberg, Jansson, & Kaijser, 2006). Aqua jogging is used as low-impact training modality for individuals with compromised joints, during rehabilitation, weight bearing restriction, or when land exercise is not tolerated.…”
Section: Introductionmentioning
confidence: 99%